Epidermal Inclusion Cyst Formation: Late Complication of Carpal Tunnel Release - Kamenko, Srdjan; Richards, Holden; Madsen, Russell Jared; Chang, Shiliang (Journal of Wrist Surgery, 2022)
Background Epidermal inclusion cysts (EIC) are epidermally lined, keratin containing cysts which occur when keratinizing epithelium becomes imbedded in deeper subcutaneous tissue, usually following penetrating trauma, or, rarely, surgery. We describe a case of an EIC presenting as a late complication following open carpal tunnel release (CTR).Case Description A 64-year-old woman with a history of left open CTR 17 years prior presented to our institution with unprovoked left palmar pain, swelling, and fluctuance. Computed tomography imaging confirmed the presence of a multiloculated abscess involving the hypothenar musculature. The abscess developed at the site of a small, pre-existing, asymptomatic mass that the patient recalls developed within months of CTR surgery. She was initially treated with antibiotics and bedside incision and drainage, but required further operative exploration in the setting of persistent erythema and drainage. An inflamed cystic structure consistent with an infected EIC was identified and completely excised. Her wound healed by secondary intention. Her postoperative course was uncomplicated. Pathology confirmed a diagnosis of EIC.Literature Review Only one other case report was found in which the patient presented within 2 years following CTR surgery with what was later confirmed to be an EIC and recurrent median nerve compression symptoms.Clinical Relevance To prevent a delay in definitive surgical care, EIC rupture and subsequent infection should be considered in the differential diagnosis when evaluating patients with a history of prior hand surgery who are presenting with an unprovoked hand abscess, as incision and drainage alone will not adequately treat an EIC.
Keywords: epidermal inclusion cyst; carpal tunnel release; complication